Novel acsF Gene Primers Revealed a Diverse Phototrophic Bacterial Population, Including Gemmatimonadetes, in Lake Taihu (China) - Huang, Yili; Zeng, Yanhua; Lu, Hang; Feng, Hao; Zeng, Yonghui; Koblížek, Michal (Applied and environmental microbiology, 2016)
UNLABELLED: Anoxygenic phototrophs represent an environmentally important and phylogenetically diverse group of organisms. They harvest light using bacteriochlorophyll-containing reaction centers. Recently, a novel phototrophic bacterium, Gemmatimonas phototrophica, belonging to a rarely studied phylum, Gemmatimonadetes, was isolated from a freshwater lake in the Gobi Desert. To obtain more information about the environmental distribution of phototrophic Gemmatimonadetes, we collected microbial samples from the water column, upper sediment, and deeper anoxic sediment of Lake Taihu, China. MiSeq sequencing of the 16S rRNA, pufM, and bchY genes was carried out to assess the diversity of local phototrophic communities. In addition, we designed new degenerate primers of aerobic cyclase gene acsF, which serves as a convenient marker for both phototrophic Gemmatimonadetes and phototrophic Proteobacteria Our results showed that most of the phototrophic species in Lake Taihu belong to Alpha- and Betaproteobacteria Sequences of green sulfur and green nonsulfur bacteria (phototrophic Chlorobi and Chloroflexi, respectively) were found in the sediment. Using the newly designed primers, we identified a diverse community of phototrophic Gemmatimonadetes forming 30 operational taxonomic units. These species represented 10.5 and 17.3% of the acsF reads in the upper semiaerobic sediment and anoxic sediment, whereas their abundance in the water column was <1%. IMPORTANCE: Photosynthesis is one of the most fundamental biological processes on Earth. Recently, the presence of photosynthetic reaction centers has been reported from a rarely studied bacterial phylum, Gemmatimonadetes, but almost nothing is known about the diversity and environmental distribution of these organisms. The newly designed acsF primers were used to identify phototrophic Gemmatimonadetes from planktonic and sediment samples collected in Lake Taihu, China. The Gemmatimonadetes sequences were found mostly in the upper sediments, documenting the preference of Gemmatimonadetes for semiaerobic conditions. Our results also show that the phototrophic Gemmatimonadetes present in Lake Taihu were relatively diverse, encompassing 30 operational taxonomic units.
Keywords: China; polymerázová řetězová reakce; geologické sedimenty; Bacterial Proteins; RNA, Ribosomal, 16S; Lakes; Sequence Analysis, DNA; ribozomální DNA; sekvenční analýza DNA; Bacteria; společenstvo; DNA Primers; jezera; Geologic Sediments; DNA, Bacterial; DNA bakterií; bakteriální proteiny; Biota; DNA primery; RNA ribozomální 16S; Polymerase Chain Reaction; Čína; DNA, Ribosomal